The educational needs of and barriers faced by Syrian refugee students in Turkey: a qualitative case study. Issue 5 (3rd September 2017) - Aydin, Hasan; Kaya, Yeliz
Abstract: The purpose of this study is to explore the educational status of Syrian refugees in Turkish schools, and the perspectives of teachers and school principals regarding the needs of Syrian refugee students in two inner‐city elementary schools in Istanbul, Turkey. A qualitative interpretive case study method was employed. Eight participants (seven teachers and one school principal), who had Syrian refugee students in their classes and wider school environment, participated in the study. The findings of the study show that Turkish public schools provide many Syrian children in Istanbul with an access to education, and a welcoming and secure learning environment. However, poor school conditions, linked to the potentially limited capacity of teachers and the shortage of sufficiently trained teachers able to instruct refugees, inadequate resources and inappropriate curriculum planning impede the provision of high-quality education.